1999
DOI: 10.1086/302423
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity Mapping of the Achromatopsia Locus in the Pingelapese

Abstract: Achromatopsia, or total color blindness (also referred to as "rod monochromacy"), is a severe retinal disorder characterized clinically by an inability to distinguish colors, impaired visual acuity in daylight, photophobia, and nystagmus. Inherited as an autosomal recessive trait, achromatopsia is rare in the general population (1:20,000-1:50,000). Among the Pingelapese people of the Eastern Caroline Islands, however, the disorder occurs at an extremely high frequency, as recounted in Oliver Sacks's popular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…A genetic deletion of Tc␣ would be expected to result in achromatopsia or rod monochromacy. This condition is quite rare, and thus far, the few cases studied arose from mutations in the cone cGMP-gated channel (42) or in another protein of unknown function (43). If cones contain some Tr␣, then subtle cone abnormalities might be present in the absence of Tr␣, and partial cone function might be retained in the absence of Tc␣.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic deletion of Tc␣ would be expected to result in achromatopsia or rod monochromacy. This condition is quite rare, and thus far, the few cases studied arose from mutations in the cone cGMP-gated channel (42) or in another protein of unknown function (43). If cones contain some Tr␣, then subtle cone abnormalities might be present in the absence of Tr␣, and partial cone function might be retained in the absence of Tc␣.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, it is caused by mutations in the cyclic nucleotide-gated (CNG) ion channel subunit A3 (α subunit) 3,4 or B3 (β subunit) of cone photoreceptors [5][6][7] . Studies performed mainly in North American and European populations have shown that mutations in the CNGB3 gene are the most common cause of ACHM, accounting for at least 50% of all cases 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…In the second case, the emphasis is not only upon the finding of excess homozygosity, but excess homozygosity for a given marker allele, as it is assumed that only one disease gene is segregating within that family. Examples include the studies by Winick et al (1999) of achromatopsia in the Pingepalese (three large kindreds with 63 individuals), van Duijn et al (2001) of earlyonset Parkinsonism in a single family from a Dutch isolate (nine individuals genotyped, of which four were affected) and Hand et al (1999) of congenital endothelial dystrophy in one large inbred Irish kindred with 28 affected individuals.…”
Section: Outline Of Homozygosity Mapping Studiesmentioning
confidence: 99%
“…This approach is applicable in samples of individuals from a single large kindred where it is reasonable to assume that the segregating disease gene is inherited from a single common ancestor. Examples include studies of achromatopsia (Winick et al, 1999), urofacial syndrome (Wang et al, 1997) and endothelial dystrophy (Hand et al, 1999). In summary, the technique consists of creating two DNA pools, one using DNA from affected individuals and the other using DNA from unaffected individuals.…”
Section: Two-stage Genotypingmentioning
confidence: 99%